Imported human malaria cases Peninsular Malaysia and its associated factors, 2015-2019 - Ismail, Mohd Hafiz Che (2021)
A total of 3061 human malaria cases have been reported in Malaysia between 2015 and 2019, and 77% of cases were imported. Despite the downward trend of locally acquired human malaria cases, there is an increasing trend of imported human malaria cases. Our study aimed to study the distribution and associated factors for imported human malaria cases in Peninsular Malaysia from 2015 until 2019. The study was conducted using surveillance data at the Ministry of Health Malaysia. Human malaria cases in Peninsular Malaysia from 2015 until 2019 reported in Vekpro Online that fulfil subject criteria were included. A simple random sampling technique was used for sampling. All data extracted from Vekpro Online were recorded in proforma. All cases were classified into locally acquired and imported human malaria. Multiple logistic regression was used to determine the factors associated with imported human malaria cases. A total of 716 cases were included, of which 89.4% were males. Most of the cases (85.3%) were in the age group 18-59 years, followed by less than 18 years (11.2%). The majority of the cases were Malaysian (68.4%), working in the agriculture, forestry, and fishing sectors (55%), having P. vivax infection (56%), have the presence of gametocyte (62.7%), having an uncomplicated infection (91.1%) and living in the rural area (59.4%). Significant association with imported human malaria were found in the age group 18-59 years (AdjOR 8.687; 95% CI: 3.631, 20.782, p-value <0.001), 60 years and above (AdjOR 7.844; 95% CI: 1.308, 47.024, p-value=0.024), male (AdjOR 8.029; 95% CI: 3.497, 18.434, p-value<0.001), foreigner (AdjOR 7.412; 95% CI: 3.009, 18.260, p-value<0.001), working in agricultural sector (AdjOR 2.680; 95% CI: 1.297, 5.536, p-value=0.008), infected with P. vivax (AdjOR 0.300; 95% CI: 0.125, 0.595, p-value=0.001), presence of gametocytes (AdjOR 0.300; 95% CI: 0.158, 0.569, p-value<0.001), and living in the rural area (AdjOR 0.055; 95% CI: 0.016, 0.190, p-value<0.001). These findings will aid the Ministry of Health Malaysia in formulating new strategies and strengthen the existing one in managing imported malaria and preventing the reintroduction of malaria into the country.